Cultural appropriation in the audiovisual industry. A socio-legal analysis of an international problem of the last twenty years - Modica Bareiro, Aldo Fabrizio (2023)
The aim of this paper is to analyze the international problem of cultural appropriation in the audiovisual industry during the last twenty years, from a sociological and legal perspective, and its linkage with intellectual property rights. It will start from a conceptualization of the term and then delimit its analysis towards traditional cultural expressions and their various forms of protection in the international arena. The economic numbers of the film industry will be known and then the study will focus on the various components of cultural appropriation in films, both in the extrapatrimonial aspects (negative representations, stereotypes, and discriminatory behaviors) and in the patrimonial aspects (unauthorized exploitation and undue economic exploitation of collective rights). Finally, a detailed study of two audio-visual works by Disney (The Lion King and Frozen), will be carried out.